An Integration of Multicultural Perspective in Musical Theatre Education Using Pattern Mining - Jialin Li; Hyuntai Kim (International Journal of Engineering, Science and Information Technology, 2026)
Musical theatre education has traditionally focused on Western techniques, limiting students' exposure to the cultural diversity inherent in the art form. Current curricula frequently lack systematic methods for incorporating non-Western traditions, resulting in an underrepresentation of practices like Chinese musical theatre. To address this limitation, this study suggests developing a culturally inclusive curriculum framework based on the Multicultural Musical Theatre Dataset (MMTD) with the Hybrid Rule-Based Similarity Matching Algorithm (HRSMA). The HRSMA combines rule-based pattern extraction through frequent pattern mining with similarity-based classification via Jaccard Similarity. This hybrid approach allows for accurate categorization of various musical theatre styles into structured curriculum themes, ensuring balanced cultural representation. Experimental results validate the model's effectiveness, with 92.5% accuracy, 91.8% precision, 93.2% recall, along with an F1-score of 92.5%, indicating both efficiency and robustness in style classification. Beyond classification, the framework promotes pedagogical inclusiveness by systematically incorporating multicultural practices into theatre education. This approach goes beyond traditional Western-centric models to boost student creativity, broaden cultural understanding, and encourage critical thinking. The combination of frequent pattern mining with similar measures demonstrates creativity in balancing cultural inclusion with data-driven curriculum design. Furthermore, the findings demonstrate the practical advantages of this approach for both educators and students. At the same time, students are exposed to a broader range of cultural expressions, which fosters a deeper appreciation for global heritage and strengthens their artistic adaptability. This dual focus ensures that the curriculum remains both academically rigorous and culturally inclusive. To summarize, the proposed HRSMA-based framework offers a reproducible, methodical, and innovative approach to broadening the scope of musical theatre education. Incorporating global cultural practices improves classification accuracy while also promoting a cosmopolitan learning environment that values diversity, encourages engagement, and strengthens appreciation for world cultural heritage in performing arts training.